The next bastion to be conquered in immunotherapy: microsatellite stable colorectal cancer - Ding, Kai; Mou, Pei; Wang, Zhe; Liu, Shuqing; Liu, JinPei; Lu, Hao; Yu, Ganjun (Frontiers in Immunology, 2023)
Colorectal cancer (CRC) is the second leading cause of cancer-related deaths worldwide, and its incidence continues to rise, particularly in developing countries.The advent of immune checkpoint inhibitors (ICIs) has represented a significant advancement in CRC treatment. Deficient mismatch repair (dMMR) or high microsatellite instability (MSI-H) serves as a biomarker for immunotherapy, with dMMR/MSI-H CRC exhibiting significantly better response rates to immunotherapy compared to proficient mismatch repair (pMMR)or microsatellite stable (MSS) CRC.While some progress has been made in the treatment of pMMR/MSS CRC in recent years, it remains a challenging issue in clinical practice. The tumor microenvironment (TME) plays a crucial role not only in the development and progression of CRC but also in determining the response to immunotherapy. Understanding the characteristics of the TME in pMMR/MSS CRC could offer new insights to enhance the efficacy of immunotherapy. In this review, we provide an overview of the current research progress on the TME characteristics and advancements in immunotherapy for pMMR/MSS CRC.